ANALISIS ISI PESAN-PESAN DAKWAH DALAM BUKU MERASA PINTAR, BODOH SAJA TAK PUNYA (KISAH SUFI DARI MADURA KARYA RUSDI MATHARI) - Bilad, Fathikul; Abdurrazaq, Muhammad N. (Journal of Islamic Studies, 2023)
Preaching is not only in front of the audience (face to face), it can be through the media as a bridge to convey Islamic teachings. Means and methods for conveying da'wah messages to mad'u through print media, including newspapers, magazines, books, and articles. Preaching essages conveyed through the writing method are considered more efficient for some mad'u. The purpose of this study was to find out the da'wah messages in the book Feeling Smart, Stupid Just Don't Have (The Story of a Sufi from Madura) by Rusdi Mathari, and to find out the most dominant da'wah messages in the book. The method used in this study is a qualitative approach using content analysis techniques which are often used to examine da'wah messages. Based on the results of the content analysis it was concluded that there were many da'wah messages, namely messages of faith, messages of sharia, and messages of morality which were the most dominant messages.